A Novel Temporary Anchorage Device Aided Sectional Mechanics for Simultaneous Orthodontic Retraction and Intrusion - Adith Venugopal; Paolo Manzano; Sri Rengalakshmi (Case Reports in Dentistry)
Closing spaces on light wires with inadequate knowledge and inappropriate mechanics can cause a “roller coaster” effect leading to an improper occlusion. Current knowledge of biomechanics, along with the incorporation of TADs, has made this process less challenging and more predictable. Resistance to sliding is considered the most prominent inhibitor of space closure in archwire-guided space closure or sliding mechanics, in turn delaying treatment duration considerably. In our case, resistance to sliding, primarily binding of the wire in the bracket slot, was nullified with the use of loop and sectional mechanics. This case report is aimed at showcasing the successful treatment of a young lady with a novel clinical setup to retract the canines into the premolar extraction space and simultaneously retract and intrude the anterior segment using sectional archwires and TADs in just under nine months. The current setup with sectional wires and TADs produced an uprighting, and an intrusive effect on the upper incisors during space closure. Additionally, the anchorage design avoided any significant change in the vertical dimension during sagittal correction of the Class II malocclusion. The occlusal plane remained almost stable with good amount of uprighting of the lower incisors following lower space closure too. The use of good biomechanical principles helped us achieve all the treatment goals and objectives in a very short period of time.